ANALISIS RASIO LIKUIDITAS DAN RASIO PROFITABILITAS UNTUK MENILAI KINERJA KEUANGAN (STUDI KASUS PADA PERUSAHAAN PT. MAHAKA MEDIA TBK ) - GRESIA SIHOMBING; TOGU HARLEN LBN. RAJA; DESYANA PUTRI (JURNAL ILMIAH KOHESI, 2022)
This study was used to determine the financial performance of PT.. Mahaka Media Tbk. The focus of this research is on the 2014, 2015, 2016, 2017, and 2018 financial statements, with financial ratios, namely liquidity ratios consisting of Quick Ratio Curent Ratio, and the Profitability Ratio consists of Return on Assets, and Return on Equity. The type of data used is secondary data and data sources using external data. The results of this study can be seen the overall liquidity ratio from 2014 to 2018 in a unhealthy state but the reduced level of liquidity for each year. The profitability ratio is very unhealthy, but decreases every year. Even though the financial statements decrease every year, PT.. Mahaka Media Tbk is still considered healthy and contributes positively to the success of its financial performance.